The participants of the Stock Exchange and the Securities Market (Journal of actual problems of jurisprudence, 2019)
According to the purpose of scientific work the legal characteristic of the financial exchange and securitiesmarket is given. It is considered features of the financial exchange and off-exchange the organizations, andalso subjects of infrastructures of securities market. In research it is discussed functions of participants ofsecurities marketKeywords: securities market, primary and secondary market, financial exchange, security, issue security,professional participants, issuer.